2018
DOI: 10.1159/000490353
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiles of Tumor Necrosis Factor-α and Endothelin-1 in Obstructive Sleep Apnea

Abstract: Background/Aims: The aim of this study was to observe the relationship between the gene expression profiles of tumor necrosis factor (TNF)-α and endothelin (EDN)-1 and obstructive sleep apnea (OSA). Methods: A prospective, cross-sectional study performed at a tertiary-care academic center; 108 patients with snoring and day-time sleeplessness were included in this study carried out in the Otolaryngology Department. All patients were evaluated with 1-night polysomnography (PSG). There were 63 patients with OSA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…22,23 TNF-α gene expression levels were significantly higher in the OSA group than in the control group. 24,25 Some studies suggested a relationship between polymorphic variation in the TNF-α gene and OSA. The −308G/A polymorphism has been associated with increased levels of TNF-α, which is involved in intermittent hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 TNF-α gene expression levels were significantly higher in the OSA group than in the control group. 24,25 Some studies suggested a relationship between polymorphic variation in the TNF-α gene and OSA. The −308G/A polymorphism has been associated with increased levels of TNF-α, which is involved in intermittent hypoxia.…”
Section: Discussionmentioning
confidence: 99%